2019
DOI: 10.3390/ijms20122953
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of the Type 1 Tyramine Receptor in the Diamondback Moth, Plutella xylostella

Abstract: Tyramine receptors (TARs) can be activated by tyramine (TA) or octopamine (OA) and have been shown to be related to physiological regulation (e.g., gustatory responsiveness, social organization, and learning behavior) in a range of insect species. A tyramine receptor gene in Plutella xylostella, Pxtar1, was cloned and stably expressed in the HEK-293 cell line. Pharmacological properties and expression profile of Pxtar1 were also analyzed. Tyramine could activate the PxTAR1 receptor, increasing the intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Similar results, i.e., yohimbine > mianserin > phentolamine > chlorpromazine, were obtained when investigating the P. xylostella TAR1 expressed in HEK 293T cells [ 47 ]. When biogenic amines different from TA and OA, such as dopamine, adrenaline, noradrenaline, L-DOPA, and histamine, were tested on TAR1s, no significant agonist effects were observed, suggesting that this receptor class is selectively responsive to TA and OA [ 40 , 42 , 44 , 45 , 46 , 47 ]. The pharmacological profile of TAR1 has been characterized especially for the antagonist, whereas our knowledge of alternative agonists is almost completely lacking.…”
Section: Tar1: Pharmacologymentioning
confidence: 99%
“…Similar results, i.e., yohimbine > mianserin > phentolamine > chlorpromazine, were obtained when investigating the P. xylostella TAR1 expressed in HEK 293T cells [ 47 ]. When biogenic amines different from TA and OA, such as dopamine, adrenaline, noradrenaline, L-DOPA, and histamine, were tested on TAR1s, no significant agonist effects were observed, suggesting that this receptor class is selectively responsive to TA and OA [ 40 , 42 , 44 , 45 , 46 , 47 ]. The pharmacological profile of TAR1 has been characterized especially for the antagonist, whereas our knowledge of alternative agonists is almost completely lacking.…”
Section: Tar1: Pharmacologymentioning
confidence: 99%
“…STKs participate in stress resistance in insects [51]. In honeybees, STKs are related to cold and heat stress [52,53]. Herein, we found that the expression levels of STK CG31145, STK A2, STK PAKm, and STK MKNK1II were upregulated by exposure to amitraz, which indicates that they are potentially involved in conferring tolerance to amitraz.…”
Section: Plos Onementioning
confidence: 78%
“…Many studies support the physiological role of TAR1 in processes such as locomotion (Saraswati et al, 2004;Schützler et al, 2019), metabolic control (Nishimura et al, 2005;Li et al, 2017;Roeder, 2020), reproduction (Hana & Lange, 2017a;Hana & Lange, 2017b) and olfaction (Kutsukake et al, 2000;Brigaud et al, 2009;Duportets et al, 2010;McQuillan et al, 2012;Ma et al, 2015;Zhukovskaya & Polyanovsky, 2017;Ma et al, 2019b). The TAR1 expression patterns mirror its functional roles because the TAR1 gene is highly expressed in the CNS, salivary glands and antennae in different insect species (Duportets et al, 2010;McQuillan et al, 2012;Wu et al, 2014;El-Kholy et al, 2015;Hana & Lange, 2017a;Ma et al, 2019a;Finetti et al, 2020). Two studies conducted in 2017 on the honeybee brain showed that TAR1 was mainly expressed at the presynaptic sites in antennal lobe OSNs and in the mushroom bodies PNs, which are essential structures for the olfactory system in insects (Synakevitch et al, 2017;Thamm et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…xylostella (Ma et al, 2019a) suggesting that TAR1 could be involved in male specific functions such as development as well as reproduction. The high brain expression of HhTAR1 correlates well with the abundance of TAR1 in CNS of numerous insect species (El-Kholy et al, 2015;Hana & Lange, 2017a;Finetti et al, 2020) where it regulates several sensory processes (Roeder et al, 2003;Lange, 2009;Ohta & Ozoe, 2014;Neckameyer & Leal, 2017).…”
Section: Discussionmentioning
confidence: 99%